(untitled) - Arnould, Eric J. (Boston, MA., 2004)
Consumers, 2nd Edition" presents a global, behavioural, eclectic and multi-disciplinary coverage of consumer behaviour. Reviewers praised "Consumers" as the most current text in the field in the areas of technology and research, and it contains illustrative examples.
Keywords: Consumer behavior.,Consumer behavior; United States